Crystallisation in water-in-cocoa butter emulsions: role of the dispersed phase on fat crystallisation and polymorphic transition - Di Bari, Vincenzo; Macnaughtan, William; Norton, Jennifer; Sullo, Antonio; Norton, Ian (Elsevier, 2016)
The present work is one of the first to focus on the role of emulsified water droplets on the crystallisation behaviour of water-in-cocoa butter emulsions under quiescent conditions (i.e. absence of any externally applied force). Cocoa butter (CB) systems were designed to progressively increase the number of heterogeneous nuclei within the CB matrix, and the crystallisation behaviour was studied at four temperatures (5 °C, 10 °C, 15 °C and 20 °C). Information on the crystallisation kinetics and polymorphism was obtained by pulsed nuclear magnetic resonance and differential scanning calorimetry, respectively. This work provides evidence that dispersed water droplets have two key effects on the phase transition of the continuous fat phase: (1) increase the crystallisation rate and (2) enhance the polymorphic evolution. Emulsions crystallised faster (larger Avrami kinetic constant) than the bulk phase at intermediate-low levels of supercooling, although the mechanisms of nucleation did not change across systems. Moreover, at all temperatures, emulsified CB evolved faster towards more stable polymorphs. In these systems, a mechanism of ‘interfacial heterogeneous templating’ seems unlikely considering that the emulsifier (polyglycerol polyricinoleate) does not crystallise. This result was attributed to the presence of an emulsifier liquid-like layer surrounding the water droplets where the polymorphic evolution could be locally enhanced by the structural re-arrangement of CB triglycerides.